FRAC Nord-Pas de Calais : Collection 1983-1990. - David, Caroline; Durozoi, Gérard; Hoet, Jan; Rérat, Alain; Teerlinck, Hilde (Dunkerque : FRAC Nord - Pas de Calais Dunkerque, 2008)
Andre, Carl ; Becher, Bernd & Hilla ; Beuys, Joseph ; Boltanski, Christian ; Brecht, George ; Brouwn, Stanley ; Buren, Daniel ; Burgin, Victor ; Cartier-Bresson, Henri ; Castiglioni, Archille ; Coleman, James ; Doisneau, Robert ; Downsbrough, Peter ; Eames, Charles ; Fabro, Luciano ; Filliou, Robert ; Riverhead (New York) ; Friedlander, Lee ; Genzken, Isa ; Geys, Jef ; Gilardi, Piero ; Graham, Dan ; Graham, Rodney ; Haacke, Hans ; Hains, Raymond ; Knoebel, Imi ; Kounellis, Jannis ; Lavier, Bertrand ; Leroy, Eugène ; LeWitt, Sol ; Lohaus, Bernd ; Long, Richard ; Lüthi, Urs ; Mariën, Marcel ; Merz, Mario ; Michals, Duane ; Michaux, Henri ; Morellet, François ; Mosset, Olivier ; Mourgue, Olivier ; Nauman, Bruce ; Oppenheim, Dennis ; Panamarenko ; Panton, Verner ; Pesce, Gaetano ; Pistoletto, Michelangelo ; Richter, Gerhard ; Toroni, Niele ; Wall, Jeff ; Warhol, Andy ; Weiner, Lawrence ; West, Franz ; Zorio, Gilberto
Geboortedatum en -plaats per kunstenaar
boek